Teaching and learning Chinese as a foreign language : a pedagogical grammar - Xing, Janet Zhiqun (Book collections on Project MUSE., 2006)
The author provides a research-based account of how to teach and learn Chinese as a foreign language, with detailed information on ways to develop a pedagogical model.